The effects of unbalance orientation angle on the stability of the lateral torsion coupling vibration of an accelerated rotor with a transverse breathing crack. (15th June 2016) - He, Qing; Peng, Huichun; Zhai, Pengcheng; Zhen, Yaxin
Abstract: The angular acceleration is taken into the consideration for the modeling of equations of coupling vibration in rotational operation. The effects of angular acceleration on the amplitude of both lateral and torsion vibration of the breathing cracked rotor are studied for the first time. The torsion influence of unbalance orientation angles is especially studied during the modeling of the Breathing behavior model of the crack with the mass eccentricity. Different from the previous study, the effects of unbalance orientation angle on the lateral torsion coupling vibration of the breathing cracked rotor are compared by logarithmic spectrum diagrams. Parametric stability of the breathing cracked rotor associated with both unbalance orientation angle and accelerations in diverse level of mass eccentricity are presented, these works have not been seen before. The numerical parametrically stability results are verified by comparing with the dynamic response of the system. Abstract : Highlights: Modeling of the cracked rotor with angular acceleration in rotational operation. The breathing behavior of the crack with different unbalance orientation angles. The effects of imposed angular acceleration on both lateral and torsion vibration. Parametric stability influence of unbalance orientation angle and accelerations.